Damage location in flexible structures using H2 and H∞ norm approaches - Bueno, Douglas Domingues [UNESP]; Marqui, Clayton Rodrigo [UNESP]; Lopes Junior, Vicente [UNESP] (My University, 2006)
Nowadays there is great interest in structural damage detection using non- destructive tests. Once the failure is identified, as for instance a crack, it is possible to plan the next step based on a predictive maintenance program. There are several different approaches that can be used to obtain information about the existence, location and extension of the fault in mechanical systems by non destructive tests. Among these methodologies, one can mention different optimization techniques, as for instance classical methods, genetic algorithms, artificial neural networks, etc. Most of these techniques, which are based on element-by-element adjustments of a finite element (FE) model, take advantage of the dynamic behavior of the system. These approaches are known as parameter updating methods, and are well described in the literature. The main goal of this paper is to use H2 and H∞ norms to obtain damage locations information. The proposal allows the identification of damaged elements in the structure, and provides information about the influence of these damages on the natural modes of the system. The paper concludes with a numerical simulation in an aluminum plate represented by a model of second order written in modal coordinates. Four structural damage cases were simulated using stiffness reduction. The results show with clarity the localization of each simulated damage; so, proving the viability of the presented methodology.
Keywords: Damage location; Predictive maintenance; PVDF sensors; PZT actuators; System norms